Carleman problem for two pairs of functions in a ring - Khachaturov, S. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider a particular case of the matrix Carleman problem for two pairs of functions in a ring and find a constructive solution of this problem. In addition, we propose an algorithm for the construction of solutions for two infinite systems of smooth transition and for a system of two singular equations of special type.